Pengaruh Pemberian Bunga Telang Terhadap Kelelahan Otot Pada Atlet Futsal UM Palopo - Imelya Putri; A. Heri Riswanto; Rachmat Hidayat (Jurnal Porkes, 2026)
Muscle fatigue is a major problem in futsal due to intensive anaerobic activity that triggers an increase in lactic acid and oxidative stress. Conventional treatments such as chemical supplements carry the risk of side effects, while the potential of natural ingredients such as butterfly pea flower (Clitoria ternatea), which is rich in antioxidants, has not been widely explored in the context of athlete recovery. This study aims to analyze the effect of butterfly pea flower drink on muscle fatigue levels in futsal athletes. The method used was an experiment with a one-group pretest-posttest design. A total of 10 active futsal athletes aged 21-22 years were selected using purposive sampling. Fatigue levels were measured using a beep test before and after the intervention of administering 250 ml of butterfly pea flower drink (3 grams of dried butterfly pea flowers brewed for 10 minutes) with a 30-minute interval. The data were analyzed using a paired sample t-test. The results showed a significant increase in the average beep test score from 21.62 (pretest) to 22.75 (posttest) with a p-value of 0.000 (p < 0.05) and a t-value of 14.215. The effect size analysis (Cohen's d) yielded a value of 4.49, which falls into the very large category. The conclusion of this study indicates that consumption of butterfly pea flower drink is associated with a significant improvement in physical performance in futsal athletes, suggesting its potential as a natural alternative to aid post-exercise recovery.